Traditional Diagnosis of Eimeria spp. in Fallow Deer at Middle Parts of Iraq - Kareem, Safaa M.; Kawan, May H. (The Iraqi Journal of Veterinary Medicine, 2020)
Eimeria is an apicomplex protozoon which affects many species of birds, domestic and wild animals including deer. This is the first study in Iraq that was designed for diagnosis Eimeria spp. in deer using traditional methods. Eighty fecal samples of Fallow deer (Damadama) were collected in different provinces in the middle part of Iraq during December 2018 to the end of September 2019. Samples were examined by direct smear and flotation with Sheather's solution. The total infection rate with Eimeria spp. was 70% (56/80), in which higher infection rate was observed in female deer (78%, 39/50). The results also showed that Fawn at age<3-11 months recorded higher rate of infection (86.3%, 19/22). Eimeria infection was more prevalent in Karbala and Baghdad provinces where recorded (73.3% and 72%) respectively, sharp increase of infection recorded during March (87.5%, 7/8). In addition, four species of Eimeria (E. crandalis, E. intricate, E. parva, and E. sordida) were detected in Iraqi deer according to morphological characterization of oocysts. This study highlighted the distribution of some Eimeria species in deer and revealed the effect of some epidemiological factors on prevalence in different middle Iraq provinces.